(untitled) (Journal of the College of Education for Women, 2019)
Developed the study idea to harvest torrential rains from the plateau of Western style economic cost little help to get the amount of water may exceed 2 billion m 3 per year (depending on the amount of rainfall in that year) has been exploited for agricultural projects or add water to the lakes and rivers. Adopted at the product issued by the oil company, the center (Daura Filtered) reduces the ability of soil to absorb and filter rain water to as much as possible and raise the proportion of surface runoff in addition to this that the product environment-friendly fades and evaporates within 3 years and recognized him in the states was used Successfully.